Lipopolysaccharide's Cytotoxicity on Human Umbilical Cord Mesenchymal Stem Cells - Mefina Kuntjoro; Eric Priyo Prasetyo; Febriastuti Cahyani; Michael Josef Kridanto Kamadjaja; Nike Hendrijantini; Harry Laksono; Primanda Nur Rahmania; Vivin Ariestania; Alexander Patera Nugraha; Igo Syaiful Ihsan; Aristika Dinaryanti; Fedik Abdul Rantam (Association of Support to Oral Health Research (APESB), 2022)
Objective: To show the cytotoxicity of Porphyromonas gingivalis lipopolysaccharide (LPS) on human umbilical cord mesenchymal stem cells (HUCMSCs) to better understand the characteristics for its application in regenerative procedures under periodontopathogen LPS influence. Material and Methods: Ultrapure Porphyromonas gingivalis LPS was used in this study. This research used a frozen stock HUCMSCs, previously confirmed by flow cytometry. The biological characteristics, such as cell morphology, proliferation, and protein expression, were screened. To check the cytotoxicity, HUCMSCs were cultured and divided into two groups, the control group and LPS group with various concentrations from 25 to 0.39 µg/mL. MTT assay was done and the cells were observed and counted. The significance level was set at 5%. Results: The percentage of living HUCMSCs on LPS group were not significantly different among concentrations (p>0.05) from 25 to 0.39 µg/mL, even though there were slight mean decrease between groups, but they were not significant. The duration of 24 hours of exposure of LPS does not significantly lower HUCMSCs viability. Conclusion: LPS does not affect the viability of HUCMSCs. The lower the concentration of LPS, the higher the viability of HUCMSCs.